Technical progress in circulating tumor DNA analysis using next generation sequencing. (February 2020) - Bai, Yunfei; Wang, Zexin; Liu, Zhiyu; Liang, Geyu; Gu, Wanjun; Ge, Qinyu
Abstract: Circulating tumor DNA (ctDNA) is tumor-derived, fragmented DNA that circulates freely in body fluids, predominantly in the peripheral blood. Recently, ctDNA analysis has been suggested as a complement to tissue biopsy in the detection and treatment of cancer. Genetic and epigenetic information specific to tumor cells, including single nucleotide variations, copy number variations, and modified methylation patterns, can be detected in ctDNA. Importantly, mutations in heterogenous tumors that could impart therapeutic resistance could be identified in ctDNA, which would aid in cancer diagnosis, prognosis, and real-time monitoring, and inform treatment with targeted therapies. However, ctDNA is still not a routinely used method for this purpose, because its detection techniques lack adequate sensitivity for reliable use in scientific studies and clinical trials. This review provides an up-to-date summary of ctDNA mutation detection methods based on next generation sequencing, highlighting their advantages and limitations, and focusing in particular on several optimized library preparation methods for improved sensitivity and specificity of ctDNA detection. Highlights: CtDNA analysis a complement to tissue biopsy in detection and treatment of cancer. CtDNA mutation detection methods based on next generation sequencing. Library preparation methods and bioinformatics innovations to improve sensitivity and specificity of ctDNA detection.